Pengaruh Role Overload, Role Conflict dan Role Ambiguity terhadap Kinerja Karyawan dengan Dukungan Sosial sebagai Moderating Variabel pada Karyawan PT Y di Surabaya - Kumalaretna, Dianing; Yulianti, Praptini (Arthavidya Jurnal Ilmiah Ekonomi, 2019)
ABSTRACT. This study aims to determine the level of job stress amongproduction employees in a manufacturing company, to measure the level ofemployee performance, and test the effect of work stress of Role Overload,Role Conflict and Role ambiguty on employee performance. Then this studyexamined the role of moderation from social support (from supervisors andcoworkers) about the relationship mentioned above. This research is aquantitative study using a questionnaire. All data were collected through asurvey and filled by 50 production workers in a manufacturing company inSurabaya. The sampling method suitable for this study. PLS method is usedfor statistical data analysis. The results showed a significant negativerelationship between role overload and performance, a non-significantnegative relationship between role conflict and performance, a negativerelationship between role ambiguity and performance. Support fromcoworkers and superiors has a significant moderating effect on roleoverload and role ambiguity.Key word: Role Overload, Role Conflict, Role Ambiguity, Job Performance,Social Support.